2015
DOI: 10.1016/j.matpr.2015.05.088
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties of Bi-Sn Diluted Alloys

Abstract: The dependences of resistivity, magnetoresistance, Hall effect and thermoEMF in the 4 -300 K temperature range and in magnetic fields up to 8 T were studied for the Bi 1-x Sn x (0 ≤ x ≤ 0.006) diluted alloys produced by the melt spinning method. The observed decrease of conductivity and magnetoresistance with doping is explained in terms of charge carriers scattering on tin atoms, whereas the shift of the Hall and Seebeck coefficients to the range of positive values is connected with enhanced contribution of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Similar effects have been reported whereby the presence of Bi in dendritic Bi–Cu alloys promotes formate production as compared to CO evolution observed on Cu–In alloys . Alloying can also enhance the electrical conductivity of electrodes as observed for PbO 2 that had been alloyed with Bi and/or Sn. It has also been demonstrated that CuSn alloys can promote CO 2 RR in the presence of [BMIM] + -based ionic liquids under nonaqueous conditions …”
Section: Introductionsupporting
confidence: 66%
“…Similar effects have been reported whereby the presence of Bi in dendritic Bi–Cu alloys promotes formate production as compared to CO evolution observed on Cu–In alloys . Alloying can also enhance the electrical conductivity of electrodes as observed for PbO 2 that had been alloyed with Bi and/or Sn. It has also been demonstrated that CuSn alloys can promote CO 2 RR in the presence of [BMIM] + -based ionic liquids under nonaqueous conditions …”
Section: Introductionsupporting
confidence: 66%
“…The cooling rate K achieved in our experiments was estimated following the relation used by Fedotov et al [52] for experiments performed under static conditions:…”
Section: Melt-spinning Processmentioning
confidence: 99%